Experimental and numerical approach to resolve particle deposition on dimpled heat transfer surfaces locally and temporally. (14th December 2020) - Deponte, Hannes; Kasper, Robert; Schulte, Simon; Augustin, Wolfgang; Turnow, Johann; Kornev, Nikolai; Scholl, Stephan
Highlights: Local and time resolved investigation of particle deposition on dimpled surfaces. Application of the HMM for LES of real-time fouling characteristics. Experimental investigations confirm the simulated fouling progression. Enhanced fouling mitigation due to dimpled heat transfer surfaces is quantified. Evaluation of the thermo-hydraulic efficiency for dimple rows. Abstract: When optimizing the performance of heat exchangers, it can be advantageous to introduce structures, such as dimples or ribs on the surface. One especially advantageous solution in terms of thermo-hydraulic efficiency is to use surfaces with spherical dimples, where heat transfer is increased at an only minor pressure loss increase. However, this surface structuring also influences the deposition of particles in aqueous suspensions. The resulting fouling is a serious problem for the design and operation of heat exchangers and can cause significant economic and ecological damage. Despite the knowledge of the importance of fouling and the resulting disadvantages, this knowledge has not been incorporated systematically into the design process, and the criteria of maximizing heat transfer and reducing hydraulic losses remain in the foreground during the design of heat exchangers. In this study, dimpled surfaces with a depth to diameter ration of 0.18, 0.26 and 0.35 were evaluated by measuring and comparing their heat transfer ability and pressure loss with and without the occurrence of particulate fouling from aqueous suspensions. The fouling resistance is used to assess the reduction in heat transfer efficiency due to particulate depositions, both local and time resolved. For the first time, a row of dimples is quantitatively assessed regarding its heat transfer efficiency under fouling conditions, and the thermo-hydraulic efficiency is determined experimentally. The results are matched against numerical investigations. The interactions of turbulent flow structures, heat transfer and particulate fouling in aqueous suspension are determined for dimpled surfaces.